(untitled) (Pedagogical Horizons, 2024)
Digitality is changing reading and writing. The starting point of this article is the question of how we should react to these changes from an academic and a school perspective and what challenges we have to face. It presents theses for discussion that, on the one hand, concern the development of reading and writing and, on the other hand, relate to the functions of reading and writing in learning processes. After the theses have been justified, the consequences for educational processes are analysed and suggestions for teaching practice are presented.